Brief overview on 2H NMR studies of polysiloxane‐based side‐chain nematic elastomers1. (12th June 2014) - Domenici, Valentina; Milavec, Jerneja; Zupančič, Blaž; Bubnov, Alexej; Hamplova, Vera; Zalar, Boštjan; Dong, Ronald Y.
<x xml:space="preserve">Abstract</x> This is a brief overview on recent studies on liquid crystalline elastomers (LCEs) based on polysiloxane chain, in the form of monodomain films, selectively 2H‐labeled in different parts of the LCE samples, i.e. on the crosslinker or mesogenic units. 2H NMR spectroscopic techniques were used to measure the temperature dependence of the quadrupolar splittings, line widths and relaxation times, T1 and T2. From these data, several information about the orientational order parameter, S, of various LCE fragments, thermodynamic features of the isotropic–nematic transition and main motional processes could be generalized for this type of elastomers. Copyright © 2014 John Wiley & Sons, Ltd.